The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Recent Advances in Proteomics Research 2015
DOI: 10.5772/61298
|View full text |Cite
|
Sign up to set email alerts
|

Neuroproteomics — LC-MS Quantitative Approaches

Abstract: Neuroproteomics is a scientific field that aims to study all the proteins of the central nervous system, their expression, function, and interactions. The central nervous system is intricate and heterogeneous, and the study of its proteome is consequently complex, with many biological questions still requiring deep investigation. For this, mass spectrometry approaches, most often coupled with liquid chromatography (LC-MS), have been the number one choice in proteomics, and over the years it has added many impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 267 publications
(420 reference statements)
0
3
0
Order By: Relevance
“…Thus allowing to isolate the fragmentation spectrum of very similar peptides within different SWATH windows and to obtain the quantification of those peptides at the fragmentation levels without interference, as performed in MRM. In addition to that, the SWATH-MS pipeline comprises an informed/targeted data analysis (extraction of quantitative data) limited to the peptides confidently identified in a previous conventional proteomics approach, ensuring that potentially all the proteins/peptides that have been identified could be quantified [18] , [19] . These characteristics of the SWATH-MS make it an appealing strategy to quantify PTMs, in particular for the study of cysteine modifications using differential alkylation that relies on the tagging of the cysteines with different reagents to induce a mass shift between reduced and oxidized peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Thus allowing to isolate the fragmentation spectrum of very similar peptides within different SWATH windows and to obtain the quantification of those peptides at the fragmentation levels without interference, as performed in MRM. In addition to that, the SWATH-MS pipeline comprises an informed/targeted data analysis (extraction of quantitative data) limited to the peptides confidently identified in a previous conventional proteomics approach, ensuring that potentially all the proteins/peptides that have been identified could be quantified [18] , [19] . These characteristics of the SWATH-MS make it an appealing strategy to quantify PTMs, in particular for the study of cysteine modifications using differential alkylation that relies on the tagging of the cysteines with different reagents to induce a mass shift between reduced and oxidized peptides.…”
Section: Introductionmentioning
confidence: 99%
“…The CNS proteome can change even with minimal alterations in the normal course of its development and/or function [39,40]. To understand the alterations and the mechanisms related to a disorder, we should analyze qualitative and quantitative changes in the complete set of proteins encoded by an organism's genome at different or specific points in time [23,41]. Proteomics can be a powerful tool since it can give a real-time evaluation of an individual state, health vs. disease, and, in an ideal scenario, predict the susceptibility to develop a specific mental disorder [4,39].…”
Section: The Search For Biomarkersmentioning
confidence: 99%
“…DiART was designed as a less expensive 6-plex isobaric labeling reagent to label amine groups of proteins and peptides and is, once more, based in a very similar structure as iTRAQ and TMT using an amine-reactive group, a balancer group, and a reporter group in the mass range of 114-119 Da. [111,117] In a study comparing DiART and iTRAQ, the authors found that DiART leads to more intense reporter ions and consequently less ratio compression, however with the DiART approach, the common fragmentation method is not advisable due to easy reporter ion fragmentation [118]. DiART has also proven to be compatible and valuable for PTM analysis as quantitative phosphoproteomic studies [119].…”
Section: Chemical Labeling Approaches: Isobaric Techniquesmentioning
confidence: 99%